Marf- and Opa1-Dependent Formation of Mitochondrial Network Structure Is Required for Cell Growth and Subsequent Meiosis in Drosophila Males. - Matsuo, T.; Yamanaka, M.; Inoue, Y.H. (International journal of molecular sciences, 2025)
Mitochondria are dynamic organelles that undergo repeated fusion and fission. We studied how the distribution and shape of mitochondria change during Drosophila spermatogenesis and whether factors that regulate their dynamics are necessary for these changes. Unlike the shortened mitochondria seen in mitosis, an interconnected network of elongated mitochondria forms before meiosis and is maintained during meiotic divisions. Mitochondria are evenly divided into daughter cells, relying on microtubules and F-actin. To explore the role of mitochondrial network structure in cell growth and meiosis, we depleted the mitochondrial fusion factors Opa1 and Marf and the morphology proteins Letm1 and EndoB in spermatocytes. This knockdown led to inhibited cell growth and failed meiosis. As a result, the spermatocytes differentiated into spermatids without completing meiosis. The knockdown also inhibited the cytoplasmic and nuclear accumulation of Cyclin B before meiosis, and Cdk1 was not fully activated at the onset of meiosis. Notably, ectopic overexpression of Cyclin B partially rescued the failure of meiosis. Many spermatids from the spermatocytes subjected to the knockdowns contained multiple smaller nuclei and abnormally shaped Nebenkerns. These findings suggest that mitochondrial network structure, maintained by fusion and morphology factors, is essential for meiosis progression and Nebenkern formation in Drosophila spermatogenesis.